2022
DOI: 10.1139/facets-2022-0002
|View full text |Cite
|
Sign up to set email alerts
|

Investing in Canada’s nursing workforce post-pandemic: A call to action

Abstract: Nurses represent the highest proportion of healthcare workers globally and have played a vital role during the COVID-19 pandemic. The pandemic has shed light on multiple vulnerabilities that have impacted the nursing workforce including critical levels of staffing shortages in Canada. A review sponsored by the Royal Society of Canada investigated the impact of the pandemic on the nursing workforce in Canada to inform planning and implementation of sustainable nursing workforce strategies. The review methods in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 74 publications
0
38
0
Order By: Relevance
“…37 As such, mitigating burnout symptoms must focus on improving nurses' work environment. 11,39,[43][44][45] Ultimately, high levels of burnout in the nursing workforce have an enormous impact not only on nurses' well-being, but on patients and the entire health care system. Finally, we found that emotional exhaustion completely mediated the relationship between COVID-19 impact and intent to leave, adding to the empirical evidence of the pandemic's influence on turnover intentions.…”
Section: Discussionmentioning
confidence: 99%
“…37 As such, mitigating burnout symptoms must focus on improving nurses' work environment. 11,39,[43][44][45] Ultimately, high levels of burnout in the nursing workforce have an enormous impact not only on nurses' well-being, but on patients and the entire health care system. Finally, we found that emotional exhaustion completely mediated the relationship between COVID-19 impact and intent to leave, adding to the empirical evidence of the pandemic's influence on turnover intentions.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic continues to have a psychological and physical impact on health care workers, especially the ICU staff dealing with the sickest patients. There is an epic level of burnout in healthcare workers resulting in significant staff shortages (Grant 2021;Tomblin-Murphy et al 2022;Hollingsworth and Schulte 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Positive role modelling and supportive leader behavior are necessary to build nurses’ trust. In a call to action by the Royal Society of Canada (2022) [ 9 ], rebuilding trust and valuing nurses are indispensable to safe quality patient care. Trust between leaders and nurses is necessary for meaningful innovations and can be facilitated through self-development techniques.…”
Section: Possible Approachesmentioning
confidence: 99%